1992
DOI: 10.1021/jf00019a043
|View full text |Cite
|
Sign up to set email alerts
|

CPMAS carbon-13 NMR study of lignin preparations from wheat straw transformed by five lignocellulose-degrading fungi

Abstract: After solid-state fermentation of wheat straw with five lignocellulose-degrading fungi, lignin was extracted and studied by CPMAS 13C NMR. The increase in the intensity of the signals in the 200-164 ppm range is evidence for the oxidative alteration of lignin. The lignins degraded by the white-rot fungi Ganoderma australe and Phanerochaete chrysosporium showed a decrease in the amounts of aryl carbons, whereas the intensity of the 33 ppm signal from saturated alkyl structures was strongly increased by the latt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
29
0

Year Published

1997
1997
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(31 citation statements)
references
References 27 publications
2
29
0
Order By: Relevance
“…3. The assignments of the most prominent NMR signals have been made in accordance with previous studies (Ludemann & Nimz, 1973;Maciel et al, 1985;Scalbert et al, 1986;Almendros et al, 1992). In NMR spectra for APPL extracted from inoculated wheat straw with NaOH, the signal at 31 p.p.m.…”
Section: Solid-state Cpmas 13c Nmrsupporting
confidence: 75%
See 1 more Smart Citation
“…3. The assignments of the most prominent NMR signals have been made in accordance with previous studies (Ludemann & Nimz, 1973;Maciel et al, 1985;Scalbert et al, 1986;Almendros et al, 1992). In NMR spectra for APPL extracted from inoculated wheat straw with NaOH, the signal at 31 p.p.m.…”
Section: Solid-state Cpmas 13c Nmrsupporting
confidence: 75%
“…protein, aliphatic acids, cinnamic acids) (Almendros et al, 1992 ;Gamble et al, 1994;Reeves & Schmidt, 1994). The variation in this signal must be confirmed by specific determination of the above mentioned compounds in APPL from uninoculated and inoculated wheat straw.…”
Section: Solid-state Cpmas 13c Nmrmentioning
confidence: 94%
“…Assignment of the principal signals of lignin in the region of the spectrum between 110 and 160 ppm (Bardet et al, 1985;Manders, 1987;Almendros et al, 1992) (Table 1) suggested that the nature of the lignin deposited in the early lignifying tissues near the intercalary meristem differed from that of the fully lignified tissues of the top of the internode. This suggests that the activities of monolignolsynthesizing enzymes are not uniform as the internode extends.…”
Section: Lignin Analysis (Cp-mas 13c-nmr and Ftlr Spectroscopy)mentioning
confidence: 99%
“…The resulting normalized 13 C CP/MAS NMR spectra are depicted in Fig. 1 (Almendros et al 1992;Gilardi et al 1995;Sun et al 2005;Zimbardi et al 1999). As can be seen, all of the acquired spectra were comprised mainly of chemical resonance values analogous to the carbohydrate region (60 to 100 ppm) and aromatic region (100 to 162 ppm).…”
Section: Structure Decomposition Analysis Of Biopretreated Corn Stovermentioning
confidence: 99%